Higher 5-HT1A autoreceptor binding as an endophenotype for major depressive disorder identified in high risk offspring – A pilot study. (30th June 2018) - Milak, Matthew S.; Pantazatos, Spiro; Rashid, Rain; Zanderigo, Francesca; DeLorenzo, Christine; Hesselgrave, Natalie; Ogden, R. Todd; Oquendo, Maria A.; Mulhern, Stephanie T.; Miller, Jeffrey M.; Burke, Ainsley K.; Parsey, Ramin V.; et al.
Highlights: Elevated 5-HT1A receptor binding potential (BPF ) is a trait marker that appears to be transmitted from parents with major depressive disorder (MDD) to their offspring. High risk (HR) offspring of MDD probands have higher 5-HT1A receptor BPF than healthy subjects. Supervised multivariate machine learning analysis of voxel-based positron emission tomography (PET) BPF maps can distinguish HR subjects from healthy subjects and may also predict those HR subjects who go on to develop MDD. Abstract: Higher serotonin-1A (5-HT1A ) receptor binding potential (BPF ) has been found in major depressive disorder (MDD) during and between major depressive episodes. We investigated whether higher 5-HT1A binding is a biologic trait transmitted to healthy high risk (HR) offspring of MDD probands. Data were collected contemporaneously from: nine HR, 30 depressed not-recently medicated (NRM) MDD, 18 remitted NRM MDD, 51 healthy volunteer (HV) subjects. Subjects underwent positron emission tomography (PET) using [ 11 C]WAY100635 to quantify 5-HT1A BPF, estimated using metabolite, free fraction-corrected arterial input function and cerebellar white matter as reference region. Multivoxel pattern analyses (MVPA) of PET data evaluated group status classification of individuals. When tested across 13 regions of interest, an effect of diagnosis is found on BPF which remains significant after correction for sex, age, injected mass and dose: HR have higher BPF than HV (84.3% higher in midbrain raphe, 40.8% higher in hippocampus, mean BPF across all 13 brain regions is 49.9% ± 11.8% higher). Voxel-level BPF maps distinguish HR vs. HV. Elevated 5-HT1A BPF appears to be a familially transmitted trait abnormality. Future studies are needed to replicate this finding in a larger cohort and demonstrate the link to the familial transmission of mood disorders.